Primary Ovarian Mucinous Carcinoma with Signet Ring Cells – Report of A Rare Case - Jaya Ganesh P; Vimal Chander R; Kanchana M P; Lakshmi Narasimhan (Journal of Clinical and Diagnostic Research, 2014)
Presence of signet ring cells in ovarian neoplasms are commonly encountered in Krukenberg tumours of ovary. Unusual presence in primary ovarian mucinous tumours may create a diagnostic difficulty. To the best of our knowledge only very few such cases have been reported in the literature indicating their rarity. We report a case of primary ovarian mucinous carcinoma with signet ring cells. The purpose of this presentation is to sensitize the pathologists to consider primary mucinous carcinoma as a differential diagnosis in tumours with signet ring cells.